MODELING CHLORELLA VULGARIS GROWTH ONTO POLYURETHANE FOAM FLUIDIZED BEDS AT OPTIMUM LIGHT INTENSITY AND CARBON DIOXIDE CONCENTRATION - ROSLI, SITI SUHAILAH (2019)
Cultivation of attached Chlorella vulgaris in fluidized-bed bioreactor was introduced to resolve the harvesting limitation in which the polyurethane foam (PU) support material was fluidizing within the culture medium, allowing the microalgal cells to form attachment and grow thereafter. Central composite design (CCD) was adopted to design the batch experiments under different light intensities (ranging from 100 to 300 μmol/m2 s) and CO2 concentrations (ranging from 2% to 12%) for determination of optimum light intensity (Iopt) and CO2 concentration (CO2opt).